2018
DOI: 10.6007/ijarbss/v8-i11/4952
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Self-Perceived Academic Cheating: An Empirical Evidence of Business Students

Abstract: For decades, academic cheating is one of the imperative topics that have been uncovered in the field of education. In fact, recent statistics on academic cheating among students in higher education institutions are reported to be on the rise. The main purpose of this study is to examine factors contributing to academic cheating behaviors among business students in a public university, in Malaysia. This quantitative research is intended to determine the relationships of internet facilities, lack of competencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This analysis suggests that this problem might also apply to the non-quantitative subjects. It is also worrying that the extent of the cheating may have increased over time (Hussein et al, 2018).…”
Section: Contribution and Limitationsmentioning
confidence: 99%
“…This analysis suggests that this problem might also apply to the non-quantitative subjects. It is also worrying that the extent of the cheating may have increased over time (Hussein et al, 2018).…”
Section: Contribution and Limitationsmentioning
confidence: 99%
“…What implications does this behaviour have on students' academic output? Hussein et al (2018) state that, for decades, the topic of academic cheating has been evaded in education. They argue recent statistics show that academic cheating among students in higher-education institutions is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Many reasons have been adduced to academic dishonesty among students. Some of these factors, as found in earlier studies, include: time-pressure; hard-courses; laziness; competition with others; coping with stress; difficultexams; minimal chances of getting caught; not serious punishments; improving one's grades; peer-pressure; fear of failure; "everybody does it"; course was useless; parents' pressure; taking a chance; lecturer does not care; low instructor-vigilance; high-course-load; not understanding questions; lack of effective study-habits; and negative attitudes (Chinamasa, Mavuru, Maphosa &Tarambawamwe, 2011;Gesinde, Gbadebo & Odusanya, 2011;Hussein, Rahman, Rusdi, Omar, & Aziz, 2018). Many studies have also identified various methods by which academic dishonesty can be carried out.…”
Section: Introductionmentioning
confidence: 99%